2019
DOI: 10.1186/s12913-019-4158-2
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and acceptability of collaborative learning in improving health worker performance on adolescent health: findings from implementation research in Moldova

Abstract: Background Collaborative learning has been shown to be effective in improving health worker performance, but relatively little is known about the feasibility or acceptability of collaborative learning in youth-friendly health services (YFHS). This paper describes the characteristics, feasibility and acceptability of a collaborative learning approach implemented in YFHS in Moldova as part of a national scaling up process. Methods We gathered and analysed data on the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This points to the importance of enabling health service providers to learn from and support each other through discussion and reflection, as well as the need for comprehensive, multi-sectoral approaches to address the wider social determinants of adolescents’ health. As noted by Lesco et al, the inclusion of sensitive themes like violence and abortion in collaborative learning sessions could contribute to changing the values and attitudes of health service providers on key issues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This points to the importance of enabling health service providers to learn from and support each other through discussion and reflection, as well as the need for comprehensive, multi-sectoral approaches to address the wider social determinants of adolescents’ health. As noted by Lesco et al, the inclusion of sensitive themes like violence and abortion in collaborative learning sessions could contribute to changing the values and attitudes of health service providers on key issues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group problem solving and collaborative learning have been shown to be effective in improving the attitudes and performance of health service providers in low- and middle-income countries [ 11–13 ]. However, few studies have assessed the feasibility and acceptability of collaborative learning in the context of adolescent health; further, the most comprehensive of these studies was conducted in a European setting [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome service provider bias in contraceptive provision in general, Solo and Festin recommend not blaming service providers, promoting sharing and learning from positive deviants, being explicit about what not being discriminative means in practice and using comprehensive approach to change behaviour [ 24 ]. This is illustrated in a study from Moldova which showed that fostering peer-sharing and learning in a safe environment can stimulate bottom-up problem definition and problem-solving and foster the development of norms and practices that are respectful and equitable in a group setting (even when they are not in the wider community in the group operates) [ 25 ]. Another study in India showed that health workers can be motivated, and their performance improved by supporting them to work as teams to achieve collective goals and rewarding them with public recognition and non-financial incentives [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Successful school-based programmes are often characterized by improved acceptability and feasibility of the intervention which is ultimately is used to sustain it [ 38 , 39 ]. The collaborative learning nature of such a programme might have been contributed to the improved feasibility [ 40 ]. The observed higher perceptions of intervention’s acceptability reported in the current study may be due to many reasons: first, the multi-sectors engagement approach contained within the SBCC framework (i.e.…”
Section: Discussionmentioning
confidence: 99%